OPTIMALISASI PEMANFAATAN DANA DESA MELALUI PENGEMBANGAN MASYARAKAT ISLAM DI KABUPATEN PRINGSEWU LAMPUNG - Nasir, Mohammad; Ghazali, M. Bahri; Yanti, Fitri (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2022)
This study aims to describe the management of activities in Pekon that utilize the potential of Natural Resources and Human Resources through the Village Fund Allocation (DDS) as outlined in the Pekon Revenue and Expenditure Budget (APBPekon) 2015 to 2020, which is managed independently by the community. Taking the background in Gadingrejo District, Pringsewu Regency, the subject in this study is the community in Gadingrejo District which consists of 23 Pekon with a population of 38,222 people using Purposive Sampling so that there are criteria in determining the sample. In this study, the author collects data through observation, interviews, and documentation. Actual data was collected using the descriptive analysis method. According to the study's findings, the village fund had a positive impact on the community, as evidenced by the collaboration between the government and the community in improving the development of village facilities and infrastructure such as the construction of roads, bridges, culverts, repairing village facilities by involving the community at all stages from planning to implementation to maintenance, and empowerment activities aimed at improving the econometric situation.